2019
DOI: 10.1108/igdr-10-2018-0108
|View full text |Cite
|
Sign up to set email alerts
|

Trade liberalization and productivity of Indian manufacturing firms

Abstract: Purpose The purpose of this paper is to assess the impact of India’s trade liberalization during the late 1990s and 2000s on productivity of manufacturing firms and verify whether the productivity-enhancing impact of reductions in input tariffs was greater than that of output tariff cuts, as found in some earlier studies. Design/methodology/approach Firm-level (company-level) data drawn from Prowess database are used for the estimation of total factor productivity (TFP) at the firm level, done by using the L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 50 publications
3
10
0
Order By: Relevance
“…The finding of a positive effect of imported materials on productivity in this study is in agreement with the findings of Goldar and Suresh (2017), Mukherjee (2017) and Satpathy et al (2017). This finding is also consistent with findings of Topalova and Khandelwal (2011) and Goldar et al (2019) in regard to the impact of imported intermediate inputs on TFP of Indian manufacturing firms.…”
Section: Model Data and Variables And Regression Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…The finding of a positive effect of imported materials on productivity in this study is in agreement with the findings of Goldar and Suresh (2017), Mukherjee (2017) and Satpathy et al (2017). This finding is also consistent with findings of Topalova and Khandelwal (2011) and Goldar et al (2019) in regard to the impact of imported intermediate inputs on TFP of Indian manufacturing firms.…”
Section: Model Data and Variables And Regression Resultssupporting
confidence: 93%
“…For example, Topalova and Khandelwal (2011) in their study of India manufacturing firms find that while the pro-competitive effect of import liberalisation (arising from reductions in tariff on imported products that compete with the output of domestic producers) had a positive effect on firm productivity, the bigger impact emerged from the improved access to imported inputs. Similar findings have been reported by Mukherjee (2014) and Goldar et al (2019). It may be added here that Goldar and Suresh (2017) have taken the share of imported materials in total materials used as an explanatory variable is a production function estimated for Indian manufacturing plants based on cross-section data for one year and have found that increases in the share of imported materials lead to increases in TFP.…”
Section: Model Data and Variables And Regression Resultssupporting
confidence: 84%
See 3 more Smart Citations